PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN PEMAHAMAN SISTEM PENCERNAAN PADA SISWA KELAS XI DI SMA SINAR ISLAM ASIA PASIFIC CARIU-BOGOR - Aulia, Riva Nur; Hadi, N; Ainy, N S (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2026)
This research explores the influence of the Problem Based Learning approach on students’ comprehension of studying the human digestive system in Biology at the high school level. This study used a quantitative correlational approach with 30 students chosen by applying simple random sampling. The data were obtained through a behavior a rating scale questionnaire to measure PBL implementation and multiple-choice tests to assess comprehension. The results show that PBL increases active participation, critical thinking, and problem-solving, leading to better understanding of the digestive system. The analysis reveals that PBL contributes about 69% to students’ comprehension, with the rest being because of other factors. To conclude, PBL significantly improves learning outcomes and is recommended as a successful approach to teaching Biology.